Communication through time - Oxlade, Chris (Macdonald Young Books, London, 1995)
"Communication Through Time" by Chris Oxlade, published in 1995. This 45-page hardcover book explores the evolution of communication methods, from early writing systems to modern technologies like the internet. It is part of the "Through Time" series, which examines various historical developments. The book is suitable for readers interested in the history of communication technologies.